Mesoporous Carbon Nanotablets Coupled with Mo2C Nanoparticles: Combining Morphology and Structure to Realize High Activity for Efficient Hydrogen Evolution. Issue 20 (26th May 2020) - Nie, Xiaorong; Guo, Tianyu; Du, Qianqian; Liu, Rui; Liu, Lu; Zhao, Ruihua; Zhang, Jie; Du, Jianping; Li, Jinping
Abstract: Transition metal carbide such as molybdenum carbide is most potential alternative to Pt catalysts for the hydrogen evolution reaction (HER). A high effective non‐noble metal electrocatalyst synthesized by the facile route isurgently needed. Herein, we designed a facile approach to synthesize molybdenum carbide nanocrystal dispersed on hexagonal carbon nanotablets possessing mesoporous structures. The electrocatalytic activities for HER were studied. The results show that as‐synthesized molybdenum carbide nanocomposites exhibit a superior HER activity and stability, with an overpotential of 176 mV to drive j =10 mA cm −2 in basic solution and a smaller Tafel slope of 52 mV dec −1 in acidic medium, implying molybdenum carbide hexagonal nanotablets have a promising application as Pt‐free electrocatalysts for HER. This strategy also opens a new way to fast synthesize other non‐noble metal electrocatalysts for various applications. Abstract : Mesoporous Carbon Nanotablets Coupled with Mo2 C Nanoparticles: Combining Morphology and Structure to Realize High Activity for Efficient Hydrogen Evolution. The carbon‐molybdenum carbide hexagonal nanotablets were synthesized by self‐assembly of tannic acid (TA) and ammonium molybdate (AM) into the polyhydroxyl‐Mo (PHOM) precursor that can be formed quickly at ambient condition. Carbonizing PHOM can avoid agglomeration of molybdenum carbide nanoparticles. The as‐synthesized carbonaceous molybdenum carbide, possessing morphology and structure advantage, exhibits excellent electrocatalytic activity and high stability for hydrogen evolution reaction in basic and acidic media.